Various Design Architectural level Power Reduction Techniques for Viterbi Decoder: A Review - J. Zunzunwala, Jyoti; Joshi, A. S (International Journal of Computer Sciences and Engineering, 2020)
The Viterbi algorithm is commonly applied in a number of sensitive usage models including decoding convolutional codes used in communications such as satellite communication, cellular relay, and wireless local area networks. The Viterbi algorithm process is similar to finding the most-likely sequence of states, resulting in sequence of observed events and, thus, boasts of high efficiency as it consists of finite number of possible states. Viterbi decoder is very important part at the receiver side in order to decode the convolutional codes. This paper briefly reviews the power reduction techniques along with their comparative analysis for designing Veterbi decoder at the receiver side of convolutional codes.